Parallel implementation of the wave-equation finite-difference time-domain method using the message passing interface - Ramadan, O; Akaydin, O; Salamah, M; Oztoprak, AY (Springer-Verlag Berlin, 2004)
The parallel implementation of the Wave Equation Finite Difference Time Domain (WE-FDTD) method, using the Message Passing Interface system, is presented. The WE-FDTD computational domain is divided into subdomains using one-dimensional topology. Numerical simulations have been carried out for a line current source radiating in two-dimensional domains of different sizes and performed on a network of PCs interconnected with Ethernet. It has been observed that, for large computational domains, the parallel implementation of the WE-FDTD method provides a significant reduction in the computation time, when compared with the parallel implementation of the conventional FDTD algorithm.
19th International Symposium on Computer and Information Sciences (ISCIS 2004) -- OCT 27-29, 2004 -- Kemer Antalya, TURKEY